2020
DOI: 10.1155/2020/8831855
|View full text |Cite
|
Sign up to set email alerts
|

NAC Supplementation of Hyperglycemic Rats Prevents the Development of Insulin Resistance and Improves Antioxidant Status but Only Alleviates General and Salivary Gland Oxidative Stress

Abstract: Previous studies based on animal models demonstrated that N-acetylcysteine (NAC) prevents oxidative stress and improves salivary gland function when the NAC supplementation starts simultaneously with insulin resistance (IR) induction. This study is the first to evaluate the effect of a 4-week NAC supply on the antioxidant barrier and oxidative stress in Wistar rats after six weeks of high-fat diet (HFD) intake. Redox biomarkers were evaluated in the parotid (PG) and submandibular (SMG) salivary glands and stim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 48 publications
2
17
0
Order By: Relevance
“…Previous studies demonstrated that rats fed the high-fat diet for 6 weeks developed hyperglycemia [ 2 , 3 , 33 ]. The inclusion of a 4-week NAC supplementation at this stage, despite the continuation of the HFD, prevented the development of IR and strengthened the cytoplasmic antioxidant systems of salivary glands [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies demonstrated that rats fed the high-fat diet for 6 weeks developed hyperglycemia [ 2 , 3 , 33 ]. The inclusion of a 4-week NAC supplementation at this stage, despite the continuation of the HFD, prevented the development of IR and strengthened the cytoplasmic antioxidant systems of salivary glands [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies demonstrated that rats fed the high-fat diet for 6 weeks developed hyperglycemia [ 2 , 3 , 33 ]. The inclusion of a 4-week NAC supplementation at this stage, despite the continuation of the HFD, prevented the development of IR and strengthened the cytoplasmic antioxidant systems of salivary glands [ 33 ]. Interestingly, NAC blocked oxidative modifications of proteins and carbohydrates and did not reduce lipid peroxidation in the cytoplasm of acinar cells of the submandibular glands of rats fed the HFD vs. the control rats.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Next, whole blood was collected from the abdominal aorta into glass tubes (to obtain serum) and EDTA tubes (to obtain plasma) and centrifuged (3000 × g, 4°C, 10 min). To protect against sample oxidation and proteolysis, the antioxidant butylated hydroxytoluene (BHT, ten μ L of 0.5 M BHT in acetonitrile per 1 mL sample; Sigma-Aldrich, Steinheim, Germany) and a protease inhibitor (Complete Mini Roche, France) were added to the collected saliva and plasma samples [ 72 , 73 ]. All samples were stored at -80°C but for no longer than six months.…”
Section: Methodsmentioning
confidence: 99%